Student nurses experience of learning in the clinical environment - Tsangari, Haritini; Saarikoski, Mikko; Leino-Kilpi, Helena; Papastavrou, Evridiki; Lambrinou, Ekaterini (My University, 2010)
The clinical learning environment is a complex social entity that influences student learning outcomes in the clinical setting. Exploration of this environment gives insight into the educational functioning of the clinical areas and allows nurse teachers to enhance students’ opportunities for learning. Since Cyprus is undergoing major reforms in nursing education, building on the experience and knowledge gained, this study aims to explore the present clinical situation and how this would impact on nursing education moves to the university. As nursing education would take on a different approach, it is assumed the learning approach would also be different, and so utilization of the clinical environment would also be improved. Six hundred and forty five students participated in the study. Data were collected by means of the clinical learning environment and supervision instrument. A statistically significant correlation was found between the sub-dimensions “premises of nursing care” and “premises of learning” indicating that students are relating learning environment with the quality of nursing care and patient relationships. The ward atmosphere and the leadership style of the manager were rated as less important factors for learning. The majority of students experienced a group supervision model, but the more satisfied students were those with a “personal mentor” that was considered as the most successful mentor relationship. The findings suggest more thorough examination and understanding of the characteristics of the clinical environment that are conductive to learning.
Keywords: Clinical environment; Learning environment; Clinical area